Women, love, and power : literary and psychoanalytic perspectives - Baruch, Elaine Hoffman (UPCC book collections on Project MUSE., 1991)
Elaine Baruch is not only among the most quiet-voiced and fair-minded of feminist writers. She is also among the most far-ranging in her scholarship, equally at ease with the writers of the Renaissance and Freud, the medieval troubadours, and our contemporary polemicists. . . instructive, absorbing, and persuasive.--Diana Trilling A lively mind is at work here and a keen and witty writer too.--Irving Howe This is a fine collection of essays. . . making many imaginative conjectures and amusing connections.--Times Literary Supplement In these essays what emerges is a history of romantic love.